Perceptions about the preceptor Dental Practitioner of the Primary Health Care in Dental education - Luz, Gabriela Walter da (2016)
The implementation of the National Curricular Guidelines for the healthcare area in Brazil and in particular, for dentistry, brought the need to integrate teaching with the Unified Health System. This integration is enabled by the experience of the students in the curricular internships within the public health service, accompanied by the preceptor, a professional who works in the service. The study aims to comprehend the perceptions of the dental practitioners, supervisor teachers and students about the preceptors of the Dentistry curricular internship in the Primary Health Care (PHC). A qualitative exploratory study was conducted through semi structured interviews with students, teachers and preceptors (n=20) linked to the graduation curricular internship of the Dental Course of the Universidade Federal do Rio Grande do Sul in the PHC services. The preceptor dental practitioner was perceived as the professional that inserts and integrates the student in the health team and the routine of the service during the internship. When he demonstrated receptivity to the student, didactic-pedagogical competence and security at work, acted as a learning facilitator. Positive experiences of preceptorship, along with a professional considered “competent”, resulted in a worker model and a colleague to the students. The student’s relation with the preceptor was not perceived as the student’s relation with the teacher in the university. The approach of the university and the preceptor, supporting him in the activities that he develops with the student in the work routine must be understood as a necessary condition for the integration teaching-service-community.